Assessment of Binding Affinity to 5-Hydroxytryptamine 2A (5-HT2A) Receptor and Inverse Agonist Activity of Naftidrofuryl: Comparison With Those of Sarpogrelate - Saida Abdel Regal Aly; Murad Hossain; Mohiuddin Ahmed Bhuiyan; Takashi Nakamura; Takafumi Nagatomo (Elsevier, 2009)
Abstract.: Naftidrofuryl is a peripheral vasodilator that has been clinically used in the treatment of intermittent claudication and dementia. It has 5-hydroxytryptamine 2 (5-HT2) antiserotonergic activity and selectively binds with the 5-HT2 receptor. The purpose of the present study is to assess the binding affinity and functional potency of naftidrofuryl to the 5-HT2A receptor, to find out the inverse agonist activity of this compound at a constitutively active mutant of 5-HT2A receptor, and finally to compare the findings with those of sarpogrelate. The investigation showed that the binding affinity (pKi) of naftidrofuryl was decreased 25- or 50-fold compared to sarpogrelate in the wild-type 5-HT2A receptor or Cys322Lys mutant receptor, respectively. Moreover, the functional potency (pKb) of naftidrofuryl was much lower compared to sarpogrelate at the 5-HT2A receptor. In addition, inverse agonist activity of naftidrofuryl was lower compared with sarpogrelate at the constitutively active mutant receptor. Thus, the data of the present study would be very important for the clarification of interaction sites of naftidrofuryl to 5-HT2A receptors and also may help to understand the mechanism of inverse agonist activity at the constitutively active mutant receptor. Keywords:: naftidrofuryl, inverse agonist activity, constitutively active mutant, sarpogrelate